2020
DOI: 10.1016/j.stem.2020.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Sliced Human Cortical Organoids for Modeling Distinct Cortical Layer Formation

Abstract: Highlights d SNOs maintain growth and laminar expansion over long-term culture d SNOs exhibit separated upper and deep cortical layers d Layer-specific WNT/b-catenin signaling regulates neuronal fate specification d DISC1 mutation causes deficits in cortical neuron fate specification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
327
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(335 citation statements)
references
References 73 publications
8
327
0
Order By: Relevance
“…The generation of cerebral organoid is a highly dynamic model of the embryonic developing brain over time 103 . Notably, cerebral organoids closely resemble neurons in the cortex and choroid plexus 36,70,104 . Our organoids exhibited similar developmental patterns, contained multiple brain cell types (e.g., NSCs, neurons, and astrocytes), and showed distinct multi-layered, cortical-like neuronal zone and choroid plexus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The generation of cerebral organoid is a highly dynamic model of the embryonic developing brain over time 103 . Notably, cerebral organoids closely resemble neurons in the cortex and choroid plexus 36,70,104 . Our organoids exhibited similar developmental patterns, contained multiple brain cell types (e.g., NSCs, neurons, and astrocytes), and showed distinct multi-layered, cortical-like neuronal zone and choroid plexus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of non-adherent organoids has bene ts at the practical level, as a major risk to long-term 2D cultures is the spontaneous detachment from cell culture plates. Further, the technology is continually evolving, for example through the development of vascularised organoids (41,42) and slice cultures which enable the formation of distinct cortical layers (43). Thus, further acceleration of organoid maturity is likely to be possible in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Lancaster's group has adopted air-liquid interface culture techniques, which improve the survival rate of neurons and the growth of axons and promotes the formation of circuits and the output of functional neurons (Giandomenico et al, 2019). More recently, it has been found that sliced neocortical organoid system can promote the continuous neurogenesis and dilation of the cortical plate; the cortical plate has distinct upper and deep cortical layers, which captures the neocortex in late human pregnancy and eliminates the restriction of growth and diffusion of brain organoids to some extent (Qian et al, 2020). These results indicate that brain organoids sliced culture can be used to study human-specific advanced cortical development and disease-related mechanisms (Figure 1).…”
Section: Sliced Brain Organoid Culturementioning
confidence: 99%